Composition-driven phase boundary and electromechanical properties in Bi0.5Na0.5TiO3-A(Mg1/3Nb2/3)O3 binary solid solutions. (29th November 2019) - Wang, Lejian; Zhang, Jingji; Jia, Xuanrui; Xing, Hongjie; Hao, Jigong; Wang, Jiangying
Abstract: A(Mg1/3 Nb2/3 )O3 (abbreviated as AMN, A=Ba, Sr and Ca) complex perovskite with tolerance factor t of 0.937–1.03 was incorporated into Bi0.5 Na0.5 TiO3 (BNT) matrix with t BNT  = 0.977 to form binary solid solutions, and the influence of dopant concentration and type on their ferroelectric and piezoelectric properties were investigated. It is found that the BNT- x CaMN system has a higher driving field, probably due to the co-contribution from smaller A-site ionic radius and larger atomic electronegativity. This study also revealed a relationship between t value of morphotropic and polymorphic phase boundary compositions for the BNT- x AMN systems and AMN end-members with t BaMN  = 1.03 >  t BNT, t SrMN  = 0.972 ≈  t BNT and t CaMN  = 0.937 <  t BNT, which complemen t s a MPB- t relation for quick predicting the approximate morphotropic and polymorphic phase boundary regions of BNT-based systems.